Computational drug Cumintrazole-analog for the treatment of mutant BRCA1 and BRCA2 proteins in breast cancer - Baseer, Shehneela; Khan, Sajid; Nouroz, Faisal (International Current Pharmaceutical Journal, 2015)
Breast cancer is the second death causing disease in the world. Breast cancer gene 1 (BRCA1) and Breast cancer gene 2 (BRCA2) are the controlling proteins of this cancer. Real capacity of BRCA1/BRCA2 is to control the cell division, repair the damaged DNA and stabilized the genetic material of the cell. In case of any mutation in these proteins, the division of breast cells will be modified and therefore the cancerous development of cells will start in breast. The essential target of study was to prepare novel synthetic compound to focus on destinations for receptor proteins, located on cells surface, which control the development or stop the multiplication of cancer cells. Subsequent to screening vast measure of information, we outlined novel in-silico medication compound for breast cancer that is able to hinder the uncontrolled development of cells. In docked edifices PHE and GLN are critical communicating build ups for BRCA1 and BRCA2 proteins. Atomic recipe of shad sample totally fulfills the Lipinski rule of five. It shows less symptoms and long resistance against breast cancer cells. We infer that our medication shad sample is better than the business drugs available in business sector. As it is non-toxic in nature and has no reactions. The proposed drug is suitable for reduction of the breast cancer in females. Baseer et al., International Current Pharmaceutical Journal, July 2015, 4(8): 410-414